2009
DOI: 10.1055/s-0029-1185377
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of a Potent Antimalarial and Antibacterial Polyacetylene fromBidens pilosa

Abstract: Diseases caused by malaria parasites and pathogenic bacteria were thought to be on the brink of eradication in the 1950-1960s, but they have once again become a serious threat to mankind as a result of the appearance of multidrug resistant strains. The spread of these multidrug resistant organisms has prompted a worldwide search for new classes of effective antimalarial and antibacterial drugs. Natural products have been recognized as highly important candidates for this purpose. Our attention has focused on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 20 publications
(44 reference statements)
2
37
0
3
Order By: Relevance
“…The treatment of fresh wounds by Bidens pilosa was cited by informats, 7 times out of the 11 citations. This plant has been found to have antimicrobial, anti-inflammatory properties and compounds that help in the wound healing process (Li-Ping et al, 2008;Tobinaga et al, 2009;Ashafa and Afolayan, 2009). Several isolated constituents of Bidens pilosa which have anti-inflammatory, antibacterial and antifungal properties have been studied (Geissberger and Sequin, 1991;Fabiana et al, 2011).…”
Section: Medicinal Plant Speciesmentioning
confidence: 97%
“…The treatment of fresh wounds by Bidens pilosa was cited by informats, 7 times out of the 11 citations. This plant has been found to have antimicrobial, anti-inflammatory properties and compounds that help in the wound healing process (Li-Ping et al, 2008;Tobinaga et al, 2009;Ashafa and Afolayan, 2009). Several isolated constituents of Bidens pilosa which have anti-inflammatory, antibacterial and antifungal properties have been studied (Geissberger and Sequin, 1991;Fabiana et al, 2011).…”
Section: Medicinal Plant Speciesmentioning
confidence: 97%
“…Different preparations of its whole plant and/or parts have been purported to treat over 40 categories of illnesses. Scientific studies, although not extensive, have demonstrated that B. pilosa extracts and/or compounds have antitumor [2836], antiinflammatory [18, 32, 3742], antidiabetic and antihyperglycemic [7, 4346], antioxidant [4749], immunomodulatory [29, 50], antimalarial [30, 51], antibacterial [5153], antifungal [53, 54], antihypertensive, vasodilatory [19, 55], and antiulcerative [17] activities. In this section, the primary pharmacological properties of B. pilosa extracts and phytochemicals are presented and discussed.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…Examples of drug resistance can be found in the species of the Plasmodium that cause malaria. It is important to search for new compounds to combat Plasmodium parasites [51]. A study of the anti-malarial activity of the leaf extracts of B. pilosa using a combination of phytochemistry and bioassays showed that compound 49 (Table 11) showed activity against a malaria parasite ( P. falciparum NF54 strain) with an IC 50 value of 6.0  μ g/mL [30].…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…Segundo Tobinaga et al (2009), por meio de dois compostos isolados da planta B. pilosa, verificou-se in vitro propriedades altamente potentes, antibacterianas e antimaláricas. A atividade contra o Plasmodium tem sido atribuída à presença de flavonoides e acetilenos (ANDRADE-NETO et al, 2004).…”
Section: Discussionunclassified